1,2-Dihydrochromeno[2,3-c]pyrrol-3-one Derivatives: Synthesis and HPLC-ECD Analysis - Tóth, László; Kiss-Szikszai, Attila; Vasvári, Gábor; Fenyvesi, Ferenc; Vecsernyés, Miklós; Mátyus, Péter; Antus, Sándor; Mándi, Attila; Kurtán, Tibor (Synlett, 2019)
Ethyl-3-formyl-6-methoxy-(2H)-chromene-2-carboxylate was transformed to N-substituted 1,2-dihydrochromeno[2,3-c]pyrrol-3-ones in a domino reductive amination–lactamization reaction. Isomerization of the double bond and the inherently labile stereogenic center was studied, and HPLC-ECD analysis of a chiral 1,2-dihydrochromeno[2,3-c]pyrrol-3(3aH)-one derivative aided by TDDFT-ECD calculation allowed configurational assignment of the separated enantiomers. Antiproliferative activity of the products was demonstrated on the CaCo-2 human epithelial colorectal adenocarcinoma cell line.
Keywords: 1,2-dihydrochromeno[2,3-c]pyrrol-3-one; isomerization; HPLC-ECD; TDDFT-ECD; antiproliferative